CALIPER Hematology Reference Standards (II): Improving Laboratory Test Interpretation in Children (Beckman Coulter DxH 520–Physician Office Hematology System) With Analytical Comparison to the Beckman Coulter DxH 900. Issue 3 (11th June 2020) - Higgins, Victoria; Tahmasebi, Houman; Bohn, Mary Kathryn; Hall, Alexandra; Adeli, Khosrow
Abstract: Objectives: The objective of this study was to establish comprehensive age- and sex-specific reference intervals for hematologic parameters in the CALIPER cohort of healthy children and adolescents. Methods: A total of 536 healthy children and adolescents (birth to 21 years) were recruited with informed consent, and whole blood samples were analyzed for 27 hematologic parameters on the Beckman Coulter DxH 520 system. Age- and sex-specific pediatric reference standards were established. Reference values obtained on the DxH 520 were also compared with data obtained on a larger laboratory-based instrument (DxH 900). Results: Most hematologic parameters showed significant age- and/or sex-specific changes during growth and development. Of the 27 hematologic parameters, all except four (mean corpuscular hemoglobin concentration, basophil percentage, low hemoglobin density, immature cell percentage) required age partitioning, and eight required sex partitioning. Conclusions: This study establishes a robust pediatric hematology reference database that will assist in more accurate test result interpretation. Our data clearly demonstrate significant variation in hematologic parameter concentrations in children and adolescents, necessitating the use of pediatric-specific reference standards.